2011
DOI: 10.1016/j.jinsphys.2011.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Dual reproductive cost of aging in male medflies: Dramatic decrease in mating competitiveness and gradual reduction in mating performance

Abstract: Although age-based effects on the reproductive success of males have been reported in several animal taxa the cost of aging on male mating success in lekking species has not been fully explored. We used the Mediterranean fruit fly, a lekking species, to investigate possible cost of aging on male reproductive success. We performed no choice and choice mating tests to test the hypothesis that aging does not affect the mating performance (mating success in conditions lacking competition) or the mating competitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 73 publications
1
23
0
Order By: Relevance
“…Thus, the hypothesis that females prefer older males despite their reduced fertilization success or viability of their offspring (JONES 2000, JONES & ELGAR 2004 does not seem to apply to C. capitata, at least when there is a choice between young and old males. The data obtained by us is in agreement with other recent studies on different populations of C. capitata (SILVA-NETO et al 2009, SHELLY et al 2011, PAPANASTASIOU et al 2011. Working with the same population used in this study, ANJOS-DUARTE et al (2011b) had found that females did not distinguish between males of 4 and 12 days of age and accepted to mate equally with both; however, they preferred four or 12 days-old males than 20 days-old ones.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the hypothesis that females prefer older males despite their reduced fertilization success or viability of their offspring (JONES 2000, JONES & ELGAR 2004 does not seem to apply to C. capitata, at least when there is a choice between young and old males. The data obtained by us is in agreement with other recent studies on different populations of C. capitata (SILVA-NETO et al 2009, SHELLY et al 2011, PAPANASTASIOU et al 2011. Working with the same population used in this study, ANJOS-DUARTE et al (2011b) had found that females did not distinguish between males of 4 and 12 days of age and accepted to mate equally with both; however, they preferred four or 12 days-old males than 20 days-old ones.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, in C. capitata, males experienced a drastic decrease in mating performance with age when competing against younger rivals. However, under no choice conditions, males as old as 50-70 d were able to obtain copulations as their younger counterparts (Papanastasiou et al 2011).…”
Section: Female Mating Preferences Under Choice or No Choice Conditionsmentioning
confidence: 86%
“…One important issue that complicates comparisons among species and studies is that the terms Byoung^and Bold^do not always mean the same ages. While in some cases the age differences are only a few days, in other cases flies are tested from emergence to senescence (Papanastasiou et al 2011;Benelli et al 2013;Harwood et al 2015). On the other hand, time of sexual maturation differ among species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although age associated changes of male mating success have been addressed in various insect species [18], [22], [23], [24] less attention has been given on effects of age on female sexual and reproductive behaviour [4], [25]. As insects age and senescence prevails the mortality risk increases, fecundity rates decrease [26], and female mating receptivity increases due to progressively limited opportunities of reproduction [27].…”
Section: Introductionmentioning
confidence: 99%